This
** preview**
has intentionally

**sections.**

*blurred***to view the full version.**

*Sign up*
**Unformatted text preview: **∑ (-1 ) n n n + 2 D (-1 ) n n n + 2 6→ ∑ (-1 ) n ln ( n ) n 2 C ln ( n ) n 2 → ∑ ( n 3 n + 1 ) n C ( n 3 n + 1 ) n n → 1 3 ∑ ne-n 2 C u-sub ∑ 2 n 3 n 4 + 4 n 2 C 2 n 3 n 4 + 4 n 2 < 2 3 n 3 ∑ (-1 ) n cos ( π n ) D (-1 ) n cos ( π n ) 6→ ∑ (-1 ) n 5 n n ! C 5 n n ! → ∑ 1 n ln ( n ) D u-sub ∑ (-1 ) n 1 n ln ( n ) C 1 n ln ( n ) → ∑ ( 1 2 + 1 n )-n D ( 1 2 + 1 n )-n 6→ ( 1 2 + 1 n )-n n → 2 ∑ 1 ( 2 n ) ! C ( 2 n ) ! ( 2 ( n + 1 )) ! → ∑ 1 √ n 3-3 C n 3/2 √ n 3-3 → 1...

View
Full Document